A experiência do técnico de enfermagem em UTI : aportes psicanalíticos sobre o cuidado e a dor - Baldo, Mariana Aguilar (2011)
The concern about the life quality of the worker who works in the health area has been highlighted by many programs of the Health Ministry. The Programa Humaniza SUS (Sistema Único de Saúde) has been developed since 2003 and one of its goal is to support the teams which work in the Health Units in some moments of crisis. From the development of some programs of the Federal Government it is necessary to understand not only the demands of the patients but also to aid the work s team in order to create conditions which promotes the life quality of the professionals in which the caring issue has its aim in the labor practice. Among the different sectors of a hospital, the unit which that critically ill patients are hospitalized who needs the use of technology and who are about to die due to poor clinical condition of these patients is the Intensive Treatment Unit (ITU). This essay intended to explore the emotional condition employed into labor of nursing technicians who work at ITU and are caregivers in their labor daily routine. In order to do that, two sections were written about this topic: a theoretical and an empirical one. On the theoretical part, it is proposed the specificities concerning the issue of taking care of someone, putting as priority the helplessness human condition which is increased facing some illness situation. In order to understand the psychic dynamic which is inherent in this condition, it is going to be used the psychoanalytical theory. The empirical section is going to be done through a qualitative methodology which is useful to investigate some particular aspects of nursing technicians experiences in the role of caregivers as health professionals in ITU environment. Some interviews where done which aimed to explore the life history, the motivation of choosing this profession, the aspects that facilitated and also those that complicated in their labor daily routine, as well as the effects that environment and profession have on their intrapsychic field and in the relationship intersubjective between caregiver and their patients. The outcomes of this study were analyzed and discussed through the Analysis of Content. Three categories were identified: Identificatory specificities of caregivers; Effects in the intrapsychic and intersubjective field; Revealing the care action- listening the caregiver. Thus, it was possible to think about the depth concerning the psychic phenomena involved in the task of taking care of someone. Psychoanalysis offered a great contribution to explore and to discuss about the complexity of the factors which are involved in the action of taking care of someone, as well as to think about the exigencies of psychic effort on those emotional demands of the ITU environment